2005
DOI: 10.1002/rsa.20064
|View full text |Cite
|
Sign up to set email alerts
|

Continuum percolation with steps in the square or the disc

Abstract: ABSTRACT:In 1961 Gilbert defined a model of continuum percolation in which points are placed in the plane according to a Poisson process of density 1, and two are joined if one lies within a disc of area A about the other. We prove some good bounds on the critical area A c for percolation in this model. The proof is in two parts: First we give a rigorous reduction of the problem to a finite problem, and then we solve this problem using Monte-Carlo methods. We prove that, with 99.99% confidence, the critical ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
212
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 99 publications
(216 citation statements)
references
References 28 publications
4
212
0
Order By: Relevance
“…Note that the claim becomes stronger as C increases; for C < 1/2 it is trivial, as (5) implies that in this case whp there is no black path P crossing R s horizontally.…”
Section: Crossing a Rectangle: Two Definitionsmentioning
confidence: 95%
See 1 more Smart Citation
“…Note that the claim becomes stronger as C increases; for C < 1/2 it is trivial, as (5) implies that in this case whp there is no black path P crossing R s horizontally.…”
Section: Crossing a Rectangle: Two Definitionsmentioning
confidence: 95%
“…The best value of p 0 in this lemma that is currently known is due to Balister, Bollobás and Walters [5], who showed that one may take p 0 = 0.8639. For us, the value of p 0 is not important.…”
Section: Lemmamentioning
confidence: 99%
“…Later, Wierman [36] used his 'substitution' method to give rigorous proofs of the values p b c (T ) = 2 sin(π/18) and p b c (H) = 1−2 sin(π/18) for bond percolation on the triangular and hexagonal lattices respectively; these values had been obtained heuristically much earlier by Sykes and Essam [33,34]. There are two further values that may be easily derived from these: the (3,6,3,6) or Kagomé lattice K is the line graph of the hexagonal lattice, so p s c (K) = p b c (H) = 1 − 2 sin(π/18). Also, the (3,12 2 ) or extended Kagomé lattice K + is the line graph of the lattice H 2 obtained by subdividing each bond of H exactly once, so ply be numbers that have no simpler descriptions than their definitions as critical probabilities.…”
Section: Introductionmentioning
confidence: 99%
“…There are two further values that may be easily derived from these: the (3,6,3,6) or Kagomé lattice K is the line graph of the hexagonal lattice, so p s c (K) = p b c (H) = 1 − 2 sin(π/18). Also, the (3,12 2 ) or extended Kagomé lattice K + is the line graph of the lattice H 2 obtained by subdividing each bond of H exactly once, so ply be numbers that have no simpler descriptions than their definitions as critical probabilities. Given the dearth of exact results, it is not surprising that much effort has been put into the estimation of critical probabilities.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation